The impact of company internal financial performance on firm value - Ikin Solikin; Muhamad Ardi Nupi Hasyim; Abdurokhim Abdurokhim (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
A critical element in assessing a company is how investors believe it will benefit from the company it is investing in. If the company succeeds in posting a large profit rate, it will motivate investors to invest in stocks to increase stock prices and stock demand. This study aims to determine whether internal financial performance has a significant effect on the value of manufacturing companies that have issued shares for the period 2014 to 2020 in Indonesia. This research is conducted by survey method to 50 manufacturing companies that have done the stock emission on Indonesia Stock Exchange. The data collecting technique is done by indirect communication technique through the instrument in the form of documentation study. This research was conducted in November 2021. Descriptive Analysis and Inferential Analysis do the data processing technique, that is, Correlation Analysis and Regression, with the analysis of variance (ANOVA). The results showed that: (1) The company's internal financial performance proportioned by its return on equity (ROE) shows good condition, with an average of 12.17% per company, the standard deviation of 14.24%; (2) Company Value measured by: (a) EMV (Equity Market Value) which is the product of P (Closing Price) x Qshares (Number of shares outstanding); (b) The book value of total debt (Debt); and (c) The book value of total assets (EBV), indicates good conditions, ie, average 33.16%, the standard deviation of 12.7%; (3) This hypothesis test shows ttable equal to 2,356 <tcount 5,402 (tcount> ttable) means that company's internal financial performance proportioned by return on equity (ROE) have a positive and significant effect to firm value 37,8% although low but quite meaningful. The researcher suggested paying attention to factors such as investment policy and dividend policy because it is strongly believed to affect stock price increase. Therefore it is proven that firm value to firm's internal financial performance proportioned by return on equity ROE) have a positive and significant effect.